Dorsal intradural spinal arteriovenous fistula associated with giant intradural spinal aneurysm, a case report - Ehsan Mohammad Hosseini; Alireza Rasekhi; Noushin Vahdat; Keyvan Eghbal; Mohammad Jamali; Abdolkarim Rahmanian; Arman Sourani; Mina Foroughi; Sadegh Baradaran Mahdavi (Clinical Case Reports, 2023)
Abstract Arteriovenous fistula and spinal aneurysms like other vascular malformations can mimic radiculopathy and low back pain. Precise imaging work combined with a hybrid endovascular‐microsurgical approach is the key element for the best clinical outcome.